Assessment of the Availability of an Offshore Installation by Stochastic Petri Net Modeling - Radim Bris (Communications - Scientific letters of the University of Zilina, 2014)
The purpose of this article is to illustrate the combination of stochastic Petri nets and Monte Carlo simulation approach for the evaluation of the production availability of a multi-state, multi-output offshore installation with operational loops. The presented test case comprises a great number of the problems encountered when dealing with probabilistic studies. The reason for using Petri net modeling is that it provides the necessary flexibility to describe the complexity of the plant and the realistic aspects of system behavior, such as a degradation and standby of components, maintenance, etc. Different production levels of the system are assessed and evaluated from both reliability and production efficiency point of view. Four selected configurations of the system are analyzed to investigate how the production efficiency and average availability are influenced by applying a preventive maintenance and an additional cold standby of component.